Elucidation Of Erk1/2/C-Myc/P53 Signaling Pathways Involved In Andrographolide-Induced Antiproliferative Activity In Human Glioblastoma Dbtrg-05mg Cell Line - Othman, Nurul Syamimi (2023)
The whole study evaluates andrographolide's anticancer effectiveness and potential molecular pathways using a glioblastoma multiforme (GBM) cell line.